EFFECT OF PLANTING DATES AND VA-MYCORRHIZA ON THE PERFORMANCE OF TURMERIC ( PERFORMANCE OF TURMERIC (CURCUMA LONGA L.) CV. SALEM - N. K. HEGDE, UTTAM TRIPURA,; P. PATIL, CHAYA (The Bioscan, 2016)
A field investigation was carried out to find out the suitable planting dates and with or without inoculation of VAMycorrhiza. Planting dates (fortnight intervals) starting from 2nd fortnight of April influenced the growth and yield of turmeric with or without inoculation of VA-Mycorrhiza. Various growth parameters (plant height, number of tillers per clump, number of leaves per clump and leaf area) of mean data were significantly varied at 180 days after planting in turmeric with or without inoculation of VA-Mycorrhiza. Highest plant height, number of tillers per clump, number of leaves per clump and leaf area were recorded by crop planted 2nd fortnight of May (102.79 cm, 9.20, 88.97, and 63.56 dm2 respectively) followed by 1st fortnight of May (96.04 cm, 8.37, 83.70, and 60.16 dm2 respectively). Fresh rhizome yield per hectare was also significantly higher by the crop planted in 2nd fortnight of May (47.32 t ha-1) followed by 1st fortnight of May (38.03 t ha-1). Similarly, the curing percentage and estimated cured yield were significantly higher by 2nd fortnight of May (34.00 % and 16.12 t ha-1, respectively) compared to the lowest in 1st fortnight of July (20.68 % and 0.98 t/ha respectively). Hence, planting of turmeric during 2nd fortnight of May with inoculation of VA-mycorrhiza is ideal under northern dry zone of Karnataka